ANALYSIS OF DIFFERENT DIAGNOSTIC METHODS IN DIAGNOSING CENTRAL SEROUS CHORIORETINOPATHY - Sh.A. Djamalova; D.Ch. Ibodullaeva; A.Sh. Aktamov (Central Asian Journal of Medicine, 2025)
Central serous chorioretinopathy (CSCR) is now common among the population depending on the way of life, and the fact that the disease occurs in middle-aged people and affects their ability to work requires timely detection of the disease and taking treatment measures. Differential diagnosis between both forms of acute and chronic CSR is important, because the clinical course of this disease and the treatment strategy require a separate approach for each of them. During the examination, when the data obtained by the use of minimally invasive methods, including optical coherence tomography (OCT) and fundus autofluorescence (FAF), are analyzed together, valuable information about the changes in the neuroepithelium (NE), pigment epithelium (PE), choroidal structures and the pathogenesis of the disease is obtained.